Cytological characterization of the bone marrow during fetal development in the alpaca (Vicugna pacos) - Calderón F., Elvis (2020)
The present study aimed to investigate the morphology and morphometry of progenitor cells from the bone marrow through cytological examination during foetal development of the alpaca (Vicugna pacos). Bone marrow samples were collected from 18 culled and clinically healthy alpaca foetuses in Pasco, Peru. The eighth and ninth ribs were removed using the cost-chondral junction as reference and smears were made with the bone marrow samples, and then stained with Wright. The percentages of cellularity for each third of pregnancy were 16 ± 0.2 (n= 3), 35 ± 0.16 (n= 5) and 78 ± 0.12 (n=10), respectively, showing the first hematopoietic cells from 201.5 days old. Through the differential count of 500 cells, the myeloid: erythroid ratio was established, being 0.47 ± 0.27 and 0.69 ± 0.19 for the first, second and last third of pregnancy, respectively. In the second third of pregnancy 10.17% of erythroid cells, 5.03% of myeloid cells and 84.80% of other cell types were detected, while in the last third it was 39.99% of erythroid cells, 26.99% of myeloid cells and 33.21% of other cell types. In the morphometric examination, hematopoietic cells revealed characteristics like those found in other species.